Post-transplantation cyclophosphamide GvHD prophylaxis after hematopoietic stem cell transplantation from 9/10 or 10/10 HLA-matched unrelated donors for acute leukemia - Lorentino, Francesca; Labopin, Myriam; Ciceri, Fabio; Vago, Luca; Fleischhauer, Katharina; Afanasyev, Boris; Kröger, Nicolaus; Cornelissen, Jan J; Lovira, Montserrat; Meijer, Ellen; Vitek, Antonin; Elmaagacli, Ahmet; et al. (Leukemia, 2021)
HLA-matching largely contributes to unrelated donor hematopoietic cell transplantation (UD-HCT) success but, due to the selective deletion of alloreactive T-cells, post-transplantation cyclophosphamide (PTCy) could modulate its negative impact on outcomes. We retrospectively compared acute leukemia patients receiving 10/10 or 9/10 HLA allele-matched UD-HCT with PTCy-GvHD prophylaxis between 2010 and 2017, reported to EBMT registry. The 100-day incidence of grade ≥2 and grade ≥3 aGvHD were comparable for 10/10 and 9/10 UD (28% versus 28%, p = 0.8 and 10% versus 8%, p = 0.5, respectively). The 2-year cGvHD and extensive cGvHD were similar between 10/10 and 9/10 UD (35% versus 44%, p = 0.2 and 21% versus 20%, p = 0.6, respectively). The 2-year nonrelapse mortality was 20% after 10/10 and 16% after 9/10 UD-HCT (p = 0.1). Relapse incidence at 2-year was 24% for 10/10 and 28% for 9/10 UD-HCT (p = 0.4). Leukemia-free survival at 2-year was the same for 10/10 and 9/10 UD (56 and 56%, p = 0.6, respectively), with comparable overall survival (62 and 59%, p = 0.9, respectively). Multivariate analysis showed no effect of HLA-matching on outcomes. An advanced disease status and patient disability remained the most important factors portending a worse survival. PTCy could alleviate the detrimental effect of HLA-allele mismatching in UD-HCT, potentially expanding the donor pool for acute leukemia patients.
Keywords: dospělí; Cyclophosphamide; akutní lymfatická leukemie; Female; Adult; ženské pohlaví; mladý dospělý; Neoplasm Recurrence, Local; Adolescent; homologní transplantace; lidé; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; příprava pacienta k transplantaci; Immunosuppressive Agents; Transplantation Conditioning; následné studie; míra přežití; Leukemia, Myeloid, Acute; prognóza; Middle Aged; retrospektivní studie; Follow-Up Studies; Male; Aged; Unrelated Donors; Young Adult; akutní myeloidní leukemie; lokální recidiva nádoru; nemoc štěpu proti hostiteli; Prognosis; Survival Rate; Transplantation, Homologous; Precursor Cell Lymphoblastic Leukemia-Lymphoma; lidé středního věku; senioři; mužské pohlaví; nepříbuzný dárce; testování histokompatibility; Histocompatibility Testing; cyklofosfamid; mladiství; Graft vs Host Disease; Retrospective Studies; imunosupresiva; Humans